2006
DOI: 10.1002/jez.a.342
|View full text |Cite
|
Sign up to set email alerts
|

Uteroglobin induces the development and cellular proliferation of the mouse early embryo

Abstract: Two-cell mouse embryos cultured in vitro in the presence of either purified rabbit uteroglobin (UG) or recombinant human UG developed and proliferated faster than controls cultured in the absence of this protein. Both the percentage of embryos developing to the blastocyst stage and the number of cells per embryo were increased. Treatment with UG for 3 hr was enough to trigger this response. The effect of UG was blocked by genistein, an inhibitor of tyrosine protein kinases, suggesting the involvement of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…It is a multifunctional protein with anti-inflammatory/immunomodulatory properties and it inhibits phospholipase A 2 activity and binds progesterone, retinols, polychlorinated biphenyls, phospholipids and prostaglandins (Mukherjee et al , 2007). In addition to its anti-inflammatory activities, uteroglobin displays anti-chemotactic and embryonic growth-stimulatory activities (Riffo et al , 2007). …”
Section: Discussionmentioning
confidence: 99%
“…It is a multifunctional protein with anti-inflammatory/immunomodulatory properties and it inhibits phospholipase A 2 activity and binds progesterone, retinols, polychlorinated biphenyls, phospholipids and prostaglandins (Mukherjee et al , 2007). In addition to its anti-inflammatory activities, uteroglobin displays anti-chemotactic and embryonic growth-stimulatory activities (Riffo et al , 2007). …”
Section: Discussionmentioning
confidence: 99%
“…UG is the main protein component of uterine secretion during implantation, and it has been suggested that it is involved in blastocyst formation, expansion and attachment (Beier 2000). It is also secreted during early pregnancy, stimulating the development and proliferation of the pre‐implantation embryo (Riffo et al. 2007; Mukherjee et al.…”
Section: Discussionmentioning
confidence: 99%
“…2011). Uteroglobin ( UG) is the main protein secreted by the uterus (Beier 2000) and has been shown to stimulate development and cell proliferation of pre‐implantation embryos (Riffo et al. 2007; Mukherjee et al.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of several growth factors were analyzed, and their results showed that they showed similar mRNA expression for octamer-binding transcription factor 4 (OCT-4) and vascular endothelial growth factor (VEGF), but robustly increased levels of insulin-like growth factor-I (IGF-I) and uteroglobin (UG) in parthenote embryos (Lu et al, 2002). The up-regulation of IGF-I and UG in parthenote embryos suggested their potential role in the alternation of the parthenote embryo development and cell proliferation (Riffo et al, 2007). UG has been involved in blastocyst formation, expansion and attachment, and could stimulate the development and proliferation of the pre-implantation embryo (Piecewicz et al, 2012).…”
Section: Regulation Of Parthenogenetic Activation Of Oocytesmentioning
confidence: 99%